Asuhan Keperawatan Keluarga Pada Tahap Perkembangan Lanjut Usia Dengan Pemberian Intervensi Jus Tomat Untuk Menurunkan Tekanan Darah Pada Ibu S Di Link Kaong Rt 01/Rw 05 Desa Cipocok Jaya Kecamatan Cipocok Jaya Kota Serang Tahun 2023. - Mita Nadia Febriaty; Alfika Safitri; Rina Puspita Sari (Jurnal Ilmiah Kedokteran dan Kesehatan, 2023)
Background: The family is the smallest unit in society which is the entry point in an effort to achieve optimal public health. The family is also referred to as a social system. Hypertension can be defined as persistent blood pressure where the systolic pressure is above 140 mmHg and the diastolic pressure is above 90 mmHg. Hypertension almost affects 26% of the adult neurological population worldwide, even by 2025, it is projected that 29% of the world's population (1.56 billion adults) will have hypertension. Data from WHO in 2013 showed that there are 9.4 million people in the world every year. Tomato juice as a non-pharmacological therapy or herbal as an alternative treatment of high blood disease. Tomatoes are fruits that contain lots of potassium, potassium can also affect the angiotensinogen renin system as an inhibitor of production. Objective: to know the intervention of tomato juice to lower blood pressure in hypertensive patients. Methods: by means of interviews, assessments and nursing care actions. Results: Case study obtained after clients were given nonpharmacological therapy tomato juice in Mrs. S significant results, where there was a decrease in blood pressure from 150/90mmHg to 120/80 mmHg. Conclusion: Tomato juice has an effect on lowering blood pressure in hypertensive patients.